Transwomen and transmen from Islamic family law perspective - Abdillah, Muhammad; Febriani, Fenti; Asmita, Sri; Lusiana (IAS Journal of Localities, 2023)
This article attempts to explain why the issue of sex change is still an important discussion topic in Islam. The phenomenon of transwomen and transmen is judged unilaterally on the basis of religious, cultural, and socio-religious doctrines. This study aims to be able to look further at the research gap from the previous studies by looking at the reception of transwomen and transmen in the view of Islamic family law as well as to discover the factors that have caused gender reassignment among transwomen and transmen. This paper has discovered that transwomen and transmen have suffered a stigma from religion and in society, and this stigma has been influenced by various economic, political, and religious, doctrinal interests. However, at the same time, there are cases that show religious legitimacy allows someone to change their gender. This research has been conducted using the literature study approach to investigate the reception of transwomen and transmen from the perspective of Islamic family law.